Factors that Influence the Decision to Pursue Studies or Work after Graduation: A Study among Final Year Undergraduates in Universiti Sains Malaysia - Kah , Chon KONG; Hon , Lian KOK; Fernandez, Jacqueline Liza (School of Social Sciences, 2015)
Postgraduate education is becoming more and more important in developed countries such as US and Europe, as well as in developing countries. The government of Malaysia is also trying to encourage students to pursue postgraduate studies by implementing policies such as MyBrain 15. The purpose of this research is to determine the factors that influence the decision to pursue postgraduate studies among final year undergraduates in Malaysia. A sample of 434 respondents from Universiti Sains Malaysia is used in this study and a logit regression is estimated to examine the factors that influence the choice to pursue postgraduate studies versus the choice to work. The findings of this study reveal that variables such as gender, academic stream, race, family income, CGPA and expected difference in future income are significantly related to the decision to pursue postgraduate studies. Policy recommendations based on the findings of this study include encouragement for males to pursue postgraduate studies, giving sufficient and sustainable financial aid, ensuring a higher premium for postgraduates, improving the university ranking and reputation as well as offering programmes with affordable fees and creating a better environment for students to study.